Diversification Discount or Premium? New Evidence from the Business Information Tracking Series - Villalonga, Belén (Journal of Finance, 2004)
ABSTRACT I use the Business Information Tracking Series (BITS), a new census database that covers the whole U.S. economy at the establishment level, to examine whether the finding of a diversification discount is an artifact of segment data. BITS data allow me to construct business units that are more consistently and objectively defined than segments, and thus more comparable across firms. Using these data on a sample that yields a discount according to segment data, I find a diversification premium. The premium is robust to variations in the sample, business unit definition, and measures of excess value and diversification.